REPRESENTATIONS SOCIOCULTURELLES DES POPULATIONS SUR LA PRATIQUE DE LA MEDECINE TRADITIONNELLE « TOPOKE » DANS LA CHEFFERIE DES BOLOMBOKI (RDC) - ASAKA John, ANGONDO; William WILONDJA WACIBA,; LODI PONGOMBO,; Jeannot WINGENGA-WI-EPENDO, (IJRDO - Journal of Social Science and Humanities Research, 2019)
The survey was about the sociocultural representations of the populations on lapratique of medicine traditional" Topoké" in the Chefferie of the Bolombokis. In this Community, the normal and abnormal or mystical illnesses whose therapists argue exist, it is about the tradi-practitioners, the male nurses and physicians and God's servants. The normal illnesses are treated by the tradi-practitioners, the male nurses or physicians all as God's Servants. The mystical illnesses are called on the other hand exclusively by the traditional therapists by incantations, of the reverences of the forebears, the prayers and convenient divinatory, of the invocations, the port of the amulets, the endoréisme, the holding of the canes, songs and dances. The sociocultural representations of these populations are real, positive and print the real mines of the autonomous medical practices. This ancestral medicine of Topoké people of the Bolombokis obeys the cannons of the customary weights remaining traced to the reality of the very determined cultural environment positively. The world of living and some deaths are open in such sort that the living communicate themselves with them died for the recovery of the supernatural illnesses and the blessings of generation in generation. The assigned objectives are the next one: To identify the main reasons of the recourse of the majority of populations of the chefferie of the Bolombokis to the traditional medicine, to Identify the representations socio-cultural of the populations of the Bolomboki chefferie on the Congolese traditional medicine, to Identify and to demonstrate the elements that contribute to the construction of this socio-cultural representation; to Identify the nature, the type of the social reports that exists between the tradi-practitioners and the patients.